ANALISIS KARAKTERISTIK MATERIAL MENGGUNAKAN PARALEL PLATE SAMPLE HOLDER PADA BROADBAND DIELEKTRIK SPEKTROMETER - Era Madona (Elektron : Jurnal Ilmiah, 2009)
Dielectric spektrometer is used to measure complex dielectric function of material which depends on the frequency. The measured in domain frequency learn about movement of dipole’s molecule and electric conductions in capasitor charging process. The most familiar measuring method of frequency area is parallel plat capasitor and four electrode system (V. Raicu et al, 1994). In this method, the measuring material is placed betwen two electroda in parallel place. This configuration produce a capasitor system which is possible to measure the complex impedance of the capasitor sample. In this research, measuring and analyzing the material characterization are done in high frequence to design circuit and development of many material. Based on this reason, this reseach uses dielectric spectrometer system with HP Impedance Analyzer 4191ª RF and frequency 1-1000 MHz. Spectrometer can be used on complex permittivity to measure the compact material. The measuring result can be implemented in high frequency range using phenomenological relaxation model. However, the accuracy of such predictions would need careful further study.